The Incremental Information Content of Capital Expenditures - Kerstein, Joseph; Kim, Sungsoo (The Accounting Review, 1995)
[We study whether capital expenditures provide value relevant information which is incremental to that of current earnings. Models in accounting or finance generally predict that investments such as capital expenditures yield information about a firm's future earnings that is not captured by current earnings, as managers respond to private information about future demand and costs through their investment decisions. Empirical research, however, has not provided consistent, strong evidence of this effect. After controlling for concurrent earnings information and size-related predisclosure information differences, we find that capital expenditures changes are strongly and positively associated with excess returns.]